1995
DOI: 10.1159/000237128
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of the Major Allergen from Apple and Its Allergenic Cross-Reactivity with Bet v 1

Abstract: The major allergen from apple extract was concentrated by anion exchange chromatography and further purified by reverse-phase HPLC. A distinct peak with a high degree of homogeneity was obtained. The isolated protein has a MW of 18 kD and specific IgE-binding capacity (immunoblotting, IgE-binding inhibition). N-terminal amino acid analyses of the allergen allowed 37 cleavages and showed 67.6% identity to Bet v 1, the major allergen of birch pollen. Enzyme immunoassay inhibition studies with serum of birch/appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Affinity chromatography also results in a mixture of different isoforms, as was reported for Mal d 1 from apple [25]. Another purification method for the natural Mal d 1 allergen is described by Fahlbusch et al [18], who used RP-HPLC and anion exchange chromatography. These methods do not exclude that isoforms are lost by selective extraction, which may lead to an altered immune reactivity as compared to the isoform mixture in the source tissue.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Affinity chromatography also results in a mixture of different isoforms, as was reported for Mal d 1 from apple [25]. Another purification method for the natural Mal d 1 allergen is described by Fahlbusch et al [18], who used RP-HPLC and anion exchange chromatography. These methods do not exclude that isoforms are lost by selective extraction, which may lead to an altered immune reactivity as compared to the isoform mixture in the source tissue.…”
Section: Resultsmentioning
confidence: 90%
“…acetone used for precipitation [17,] and TFA and ACN, used as components in RP-HPLC protocols [18]. Other methods such as affinity chromatography may be selective for specific epitopes and might thus lead to the loss of isoforms during purification.…”
Section: Introductionmentioning
confidence: 99%
“…An allergic reaction to apples that consists mainly of oral itching and swelling is very common in people who are also allergic to birch pollen (Lahti et al, 1980;Dreborg, 1988;Ebner et al, 1991;Vieths et al, 2002). Immunoblotting studies show sharing of allergenic epitopes leading to the cross-reactivity of IgE antibodies (van Ree and Aalberse, 1993;Fahlbusch et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…N-terminal sequencing of Mal d 1 showed that the sequence shared 62% (over 25 amino acids; Vieths et al, 1994a) and 67.6% identity (over 37 amino acids; Fahlbusch et al, 1995) to Bet v 1. Furthermore, antibodies to Bet v 1 also cross-reacted with this protein (Ebner et al, 1991Vieths et al, 1994b).…”
Section: Introductionmentioning
confidence: 99%
“…The MAbs 1D6, 2B2 and 3F8 were obtained after immunization of BALB/c mice with purified Mal d 1 as described (Fahlbusch et al, 1995). All antibodies belonged to the IgG1 subclass.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%